An investigation of ensemble-based assimilation of satellite altimetry and tide gauge data in storm surge prediction - Etala, Paula (2015)
Cyclogenesis and long-fetched winds along the southeastern coast of South America may lead to floods in populated areas, as the Buenos Aires Province, with important economic and social impacts. A numerical model (SMARA) has already been implemented in the region to forecast storm surges. The propagation time of the surge in such extensive and shallow area allows the detection of anomalies based on observations from several hours up to the order of a day prior to the event. Here, we investigate the impact and potential benefit of storm surge level data assimilation into the SMARA model, with the objective of improving the forecast. In the experiments, the surface wind stress from an ensemble prediction sys- tem drives a storm surge model ensemble, based on the operational 2-D depth-averaged SMARA model. A 4-D Local Ensemble Transform Kalman Filter (4D-LETKF) initializes the ensemble in a 6-h cycle, assimilating the very few tide gauge observations available along the north- ern coast and satellite altimeter data. The sparse coverage of the altimeters is a challenge to data assimilation; how- ever, the 4D-LETKF evolving covariance of the ensemble perturbations provides realistic cross-track analysis incre- ments. Improvements on the forecast ensemble mean show the potential of an effective use of the sparse satellite altime- ter and tidal gauges observations in the data assimilation prototype. Furthermore, the effects of the localization scale and of the observational errors of coastal altimetry and tidal gauges in the data assimilation approach are assessed.